Taṭbīq al-Imlā’ al-Manẓūr bi al-Kharīṭah aż-Żihniyyah Li Tarqiyah Qudrah aṭ-Ṭullāb Fī Tarkīb al-Jumal al-Mufīdah (Dirāsah Tajrībiyah Li al-Marḥalah al-`Āliyah Bi Ma`had Dār al-`Ulūm al-`Aṣrī Banda Aceh) - Isna Isna; Azman Ismail; Buhori Muslim (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2021)
Imlak is the activity of changing sounds that can be understood into written symbols, but these letters are placed in the correct position of words, to correct the pronunciation and meaning desired. The title of this research is